Sounding the Authentic Self: - Colin Andrew Lee (Voices, 2019)
This piece is a queer autoethnographic cycle of words, poems, and improvisations that reflect my lived experience as a queer music therapist. The improvisations come from a two-day recording session held at the Maureen Forrester Hall, Wilfrid Laurier University, Canada. By expressing my identity as a queer music therapist, I came to understand with greater clarity the therapeutic-creative process that was central to my work with clients. The music offered as part of my contribution to this queering music therapy special issue acknowledges the courage and peace needed to embrace my intersecting identities as a composer–music-therapist and a queer cisgender man.